Compact hybrid noise control system: ANC system equipped with circular noise barrier using theoretically calculated control filter. (January 2022) - Lee, Sanghyeon; Park, Youngjin
Abstract: This paper proposes and investigates the feasibility of a compact noise control system for a wide frequency band, which can be easily installed and calibrated. Noise reduction over the workspace can be achieved by noise barriers, but becomes ineffective in low-frequency. Active noise control (ANC) is effective noise control method in low-frequency, so hybrid noise control systems combining a barrier and ANC were proposed. However, previous researches aimed at global noise control behind a large barrier for a stationary environment, which is very costly and difficult to reinstall. Despite its advantages in terms of space, cost, and mobility, a compact hybrid noise control system which is ANC system equipped with a compact size barrier for a specific space has been rarely studied due to the complex scattering effects and microphone arrangements in the control space. The present study aimed to investigate the feasibility of a compact hybrid noise control system using a theoretically calculated control filter, without microphones arrangement. Thus, can be various shapes of barrier and speaker arrangements, in this study, an axisymmetric structure is dealt with, since the theoretical equations had already been established and the computational amounts are reduced by simplifying it to two-dimensional problems. Theoretical noise reduction performance of a barrier, ANC, and the proposed noise control system are compared. Performance of ANC decreases with increasing frequency, and barrier is only effective in high-frequency bands. In contrast, the proposed noise control system achieved satisfactory noise reduction throughout the entire frequency range of interest. Following that, applying the theoretically calculated control filter was validated through experiments. The results showed that the proposed noise control system achieved a noise reduction of about 8 dB for a band-limited white noise in which the frequency range is 200–2000 Hz.